2000
DOI: 10.1093/brain/123.12.2373
|View full text |Cite
|
Sign up to set email alerts
|

The neurological basis of developmental dyslexia: An overview and working hypothesis

Abstract: Five to ten per cent of school-age children fail to learn to read in spite of normal intelligence, adequate environment and educational opportunities. Thus defined, developmental dyslexia (hereafter referred to as dyslexia) is usually considered of constitutional origin, but its actual mechanisms are still mysterious and currently remain the subject of intense research endeavour in various neuroscientific areas and along several theoretical frameworks. This article reviews evidence accumulated to date that fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
336
1
33

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 542 publications
(382 citation statements)
references
References 191 publications
12
336
1
33
Order By: Relevance
“…The DTI results in the reading-impaired (adult) individuals thus reflect the disruption of a normal (anatomical and functional) connection between cooperating brain regions. Our results, however, reflect normal variations in healthy children that correlate with their individual, overall cognitive abilities as measured by a broad range of tasks in a test of "general" intelligence (which is normal in most dyslexic individuals (Habib 2000)). To further investigate we looked at the average FA from the ROI of correlated voxels in the slice at Z = +25 in left temporo-parietal white matter (detailed in Figure 1) and computed the partial correlation coefficients for the average FA versus Full-scale IQ (R = 0.58), Verbal IQ (R = 0.6), and Performance IQ (R=0.43), with subject age as the covariate, indicating that the majority of the FA differences in this area may be traced to verbal proficiency.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…The DTI results in the reading-impaired (adult) individuals thus reflect the disruption of a normal (anatomical and functional) connection between cooperating brain regions. Our results, however, reflect normal variations in healthy children that correlate with their individual, overall cognitive abilities as measured by a broad range of tasks in a test of "general" intelligence (which is normal in most dyslexic individuals (Habib 2000)). To further investigate we looked at the average FA from the ROI of correlated voxels in the slice at Z = +25 in left temporo-parietal white matter (detailed in Figure 1) and computed the partial correlation coefficients for the average FA versus Full-scale IQ (R = 0.58), Verbal IQ (R = 0.6), and Performance IQ (R=0.43), with subject age as the covariate, indicating that the majority of the FA differences in this area may be traced to verbal proficiency.…”
Section: Discussionmentioning
confidence: 42%
“…They found a positive correlation of FA in a left temporo-parietal area with higher reading skills, and the spatial location of that region is extremely close to the region exhibiting changes in FA with general cognitive ability (Figure 1, middle slice, middle row). Reading is a task that heavily relies on highly specialized brain areas in frontal, temporo-parietal, and occipito-temporal regions and their fast and efficient connection (Habib 2000;Pugh, et al 2000). In fact, it has been hypothesized that in reading-impaired individuals, "temporo-parietal difficulties disrupt this developmental trajectory" (Pugh, et al 2001), which is consistent with neuroimaging studies demonstrating pathological patterns of posterior activation in reading-impaired subjects, with a compensatory shift involving stronger activation in frontal areas (Pugh, et al 2001).…”
Section: Discussionmentioning
confidence: 63%
“…Theories based on anatomical, physiological and behavioral disorders try to explain the etiology of dyslexia, and two of them are more broadly discussed (2)(3)(4) . The first and oldest one affirms that difficulties are phonological in origin and comprise a purely linguistic deficit, that is, difficulties concern specifically one aspect of the language processing (2,3) .…”
Section: Introductionmentioning
confidence: 99%
“…The first and oldest one affirms that difficulties are phonological in origin and comprise a purely linguistic deficit, that is, difficulties concern specifically one aspect of the language processing (2,3) . The second one, which will be studied in this research, concerns perceptual sensory disorders found in people with dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…Tem sido reconhecido que alterações no processamento temporal podem ser atribuídas a sinais cognitivos e motor-perceptuais, comumente associados a desordens no aprendizado 25 . Além disso, crianças com essas desordens têm capacidade limitada de assimilar informações e precisam de mais tempo para realizá-las em um contexto de atividades motoras 10 .…”
Section: Perfil Motorunclassified